Advertising and promotion in the jewellery industry : a guide to the Trade Practices Act. - Australian Competition and Consumer Commission ([Dickson, A.C.T. : Australian Competition & Consumer Commission], 2005)
This guide provides practical information to members of the jewellery industry manufacturers, wholesalers, retailers and valuers about their obligations under the consumer protection provisions of the Trade Practices Act. It is an important resource for anyone who promotes or advertises goods and services in the jewellery industry and includes an easy reference advertising checklist to facilitate compliance with the Act.
"August 2005".
Also available in electronic versions via the Internet. Address as at 25 October 2005: http://www.accc.gov.au/content/item.phtml?itemId=706665&nodeId=file434b61086cdb0&fn=Jewellery%20industry%20guide_Aug2005.pdf
System requirements: Adobe Acrobat reader required to view/print pdf files.
Keywords: Australia; Advertising -- Jewelry -- Law and legislation -- Australia; Advertising laws -- Australia